2019
DOI: 10.1093/her/cyz010
|View full text |Cite
|
Sign up to set email alerts
|

A culturally and linguistically salient pilot intervention to promote colorectal cancer screening among Latinos receiving care in a Federally Qualified Health Center

Abstract: Despite established benefits, colorectal cancer (CRC) screening is underutilized among Latinos/Hispanics. We conducted a pilot 2-arm randomized controlled trial evaluating efficacy of two intervention conditions on CRC screening uptake among Latinos receiving care in community clinics. Participants (N = 76) were aged 50–75, most were foreign-born, preferred to receive their health information in Spanish, and not up-to-date with CRC screening. Participants were randomized to either a culturally linguistically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…A total of 10 studies were included in this review. Eight studies were conducted in the United States [31][32][33][34][35][36][37][38], while the remaining two took place in New Zealand [39] and Iran [40]. Eight studies were randomized controlled trials [31][32][33]35,[37][38][39][40]; another two had quasi-experimental designs [34,36].…”
Section: Characteristic Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 10 studies were included in this review. Eight studies were conducted in the United States [31][32][33][34][35][36][37][38], while the remaining two took place in New Zealand [39] and Iran [40]. Eight studies were randomized controlled trials [31][32][33]35,[37][38][39][40]; another two had quasi-experimental designs [34,36].…”
Section: Characteristic Of Studiesmentioning
confidence: 99%
“…Four studies followed their patients for a minimum of 3 months [32,35,38,39]; one for 4 months [40]; two for 6 months [33,37]; and one each for 12 months [36], 14 months [31], and the maximum duration of 24 months [34]. The majority of studies reported interventions targeting eligible patients [31][32][33][34][35][36][37][38]40]; one study targeted non-adherence patients [39].…”
Section: Characteristic Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations